Effect of Time and Depth of Sowing on Germination and Seedling Growth of Buchanania lanzan Spreng. - Bajpai, C.K.; Yadav, M.P.; Tewari, R.K. (Indian Journal of Agroforestry, 2020)
Buchanania lanzan Spreng., commonly known as Chironjee is an important dry fruit. To study the effect oftime and depth of sowing on germination and growth of chironjee, a field experiment with 48 treatment combinations was conducted with three replications in the nursery of department of Horticulture, Janta College, Bakewar (Etawah), U.P. in Randomized Block Design. Seeds were collected during May, 2003 from middle aged elite trees located in Rajgarh village of Pali Forest Range, district Lalitpur, Uttar Pradesh. Data were recorded on seed germination, seedling growth and biomass production of seedlings. Seed sown in the March took minimum period to initiate and complete germination at 1cm depth, while sowing in November registered maximum period to initiate and complete germination at similar depth. There was no germination in December and January at any sowing depth. Similarly, seeds sown at 4 cm depth did not germinate at all. Seed germination was significantly affected by the time of sowing. Plant growth decreased with increase in depth of sowing. However, month of sowing played major role in determining plant growth and biomass yield.